RIGHT OF MIGRANT WORKERS TO OCCUPATIONAL HEALTH AND SAFETY UNDER MALAYSIA LAWS - Aminuddin Mustaffa; Cherifi Noura; Md. Mahbubul Haque, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The migration of people to other countries in search of employment is a common phenomenon that has occurred throughout history. While migration is a positive and empowering experience, migrant workers can be vulnerable to human rights violations. In this context, international laws have provided the international legal framework on the rights of migrant workers. Among the fundamental rights of migrant workers is the right to occupational health and safety within which a worker is expected to perform his job. This paper aims to examine the right of migrant workers to occupational health and safety in light of international standards and Malaysian laws. It adopts qualitative research of doctrinal and comparative nature. It will examine the adequacy of current laws in recognizing and protecting the rights of migrant workers to occupational safety and health with reference to the standards set by the international instruments. The paper also attempts to identify factors that contributed to the high number of occupational accidents. The paper concludes that the current Malaysian laws provide a specific legal framework that aims to protect the right of migrant workers to occupational health and safety. However, non-compliance with law requirements and lack of enforcement has contributed to the high number of occupational accidents. In conjunction with that, the paper provides recommendations towards improving the Malaysian legal framework on occupational health and safety.